Naturopathic Therapy Efforts: Potential Gingerol Content in Ginger (Zingiber officinale) As An Antidiabetic - Fitri Yani Rahmawati; Yuli Rahmawati Utami; Muna Az Zahra; Ida Maryati (Universitas Padjadjaran, 2022)
Diabetes Mellitus (DM) is caused by unhealthy lifestyle habits and one of the treatment efforts is naturopathic therapy by utilizing the gingerol content in red ginger (Zingiber officinale). The role of nurses in complementary fields as providers of interventions can improve public health status. This narrative review aims to interpret research the potential content of red ginger as an antidiabetic. The research were carried out by identifying research questions,